Xerothermic grasslands of Pilica surroundings - diversity, threats and directions of changes - Babczyńska-Sendek, Beata; Kloczkowska, Agata; Błońska, Agnieszka (Biodiversity: Research and Conservation, 2012)
Xerothermic grasslands from three stands in the surroundings of the town of Pilica in the Kraków-Częstochowa Upland were investigated. It was ascertained that they represent two phytosociological units: Adonido-Brachypodietum (with two variants) and Silene otites-Thymus austriacus community. Moreover, phytocoenoses with a high contribution of xerothermic plants (Thymus-Anthyllis vulneraria community) were found in some places on the abandoned fields. On the basis of the comparison of new data and old phytosociological relevés, only slight changes over 30 years were observed. The differences concerned mostly the coverage of particular species. However, some plants disappeared and other were new (e.g. seedlings of trees and shrubs). Generally, these species were not too frequent and had inconsiderable cover. The changes which occurred manifested themselves also in the differences of mean values of some ecological indicators and in the increase of competitors, as well as clonal species.